Testing of selected hybrids of Ribes nigrum L. in Estonia - Ave Kikas; Asta-Virve Libek (Proceedings of the Estonian Academy of Sciences)
The experiment was carried out in the years 2020â2022 at the Estonian University of Life Sciences, Polli Horticultural Research Centre, with 16 prospective blackcurrant hybrids. The aim of the experiment was to study the agronomical and fruit quality traits of the selected hybrids and to identify the genotypes with the best properties. The following traits were recorded: phen ology, winter hardiness, resistance to Sphaerotheca mors-uvae Schw., Drepanopeziza ribis Kleb. and Mycosphaerella ribis Lind., the number of flowers and berries in a cluster, the drop of flowers and unripe berries as well as the yield and weight of the berries. Among the bio chemical characteristics, the content of soluble solids (Â°Brix), total acids and ascorbic acid in the berries of the most promising genotypes were determined. Genotypes 14-11-4 (SRI9154-3 Ã âKarriâ), 11-13-3 (âKatyushaâ Ã âBen Finlayâ) and 9-13-2 (âMinaj Smyriovâ Ã âBen Finlayâ) were shown to be winter-hardy, disease-resistant and associated with good yield potential, a high number of fruits per cluster and a high ascorbic acid content in the berries.